Bolshevism, Stalinism and the Comintern
X, 319 p.
Keywords: Bringing together leading authorities and cutting edge scholars, this collection re-examines the defining concepts of Stalinism and the Stalinization odel. The aim of the book is to explore how the common imperatives of a centralized movement were experienced across national boundaries.